Penggunaan Literasi Informasi untuk Pengembangan Watak Kewarganegaraan: Interaksi antara Pendidikan Kewarganegaraan , Teknologi dan Bahasa - Hidayah, Yayuk; Kurniawan, Itok Dwi; Ginusti, Gallis Nawang (Universitas Muhammadiyah Ponorogo, 2023)
Studies on civic disposition recently have been carried out with an emphasis on building moral character. However, very few have explored the use of information literacy for fostering civic disposition that examines the interaction between citizenship education, technology, and language. The goal of this research is to discover how to promote civic disposition which focuses on the interaction between citizenship education, technology, and language in the Citizenship Education course. This study used a descriptive qualitative method, which was located at Yogyakarta State University. Data were collected through interviews, observation, documentation, and literature readings. The research conclusions indicate that fostering civic disposition through information literacy in Citizenship education courses enables students to 1) strengthen their critical thinking skills, 2) learn about civic affairs prudently and effectively, and 3) become self-reliant (independent) members of society. The development of civic disposition through information literacy in Citizenship education courses at Yogyakarta State University is considered as good. through this article, the researchers conclude that fostering students’ Civic Disposition in Citizenship Education courses through information literacy is a form of habituation to smart and good citizenship.